Spectroscopic Study of the Role of Metal Ions in the Adsorption Process of Phosphate in Nanoscaled Adsorbers Based on Metal (Zn/Fe/Zr) Oxyhydroxides - Szczerba, W.; Schneider, M.; Zukrowski, Jan; Buzanich, A. Guilherme; Riesemeier, H.; Sikora, Marcin; Mandel, Karl (Journal of Physical Chemistry C, 2017)
Currently great effort is made to find materials and technologies for the recycling of phosphate from wastewater. Herein, we present an in-depth study of the phosphate adsorption mechanism of a promising adsorber material, a Zn-Fe-Zr oxyhydroxide-based nanostructured precipitate. The behavior of the multicomponent nanomaterial, consisting of both crystalline and amorphous parts, is investigated via X-ray absorption fine structure spectroscopy and Mössbauer spectroscopy, revealing the importance of the nanostructured composition for the phosphate adsorption. We found evidence that adsorption takes place especially in the vicinity of iron sites in the amorphous part of the material.
CRIS-Team Scopus Importer:2020-04-02